Глибини термодинамічної рівноваги вуглеводневих сумішей, що формують газові та газоконденсатні родовища Дніпровсько-Донецької западини - Храмов, В.; Хоха, Ю.; Любчак, О. (Геологія і геохімія горючих копалин, 2010)
З позицій класичної термодинаміки розглянуто основні стадії перетворення суперглибинного флюїду з утворенням вуглеводневої компоненти. Запропоновано ділення земної кори та мантії на зони перетворень. Для кожної зони наведено опис та
пояснення.
Опрацьовані дані по 171 газовому, газоконденсатному та нафтогазоконденсатному родовищах Дніпровсько-Донецької западини (ДДЗ). Проведено розрахунок
рівноважних глибин утворення для 118 родовищ.
Побудовано картосхеми полів глибин для ДДЗ. Методом поліноміальної регресії показано рівномірне збільшення значень рівноважних глибин у північно-західному напрямку від 80 до 150 км.
Методом тріангуляції з наступною лінійною інтерполяцією відображені локальні ускладнення положення та конфігурації зони рівноваги. Деякі з ускладнень мають
концентричні замкнуті контури, крім того, такі кільцеві форми можуть бути як “від’ємними”, так і “додатними”.
Побудовано графік розподілу глибин утворення для родовищ ДДЗ, який має два
виражені максимуми – для глибин в районі 115 та 140 км, та один слабко виражений
– для глибин 170–180 км. The main stages of the transformation of superdeep fluid with the formation of a hydrocarbon component are considered from the position of classical thermodynamics. We
have proposed the division of the earth's crust and mantle into zones of the following
transformations (depth ranges are given in km):
1. Zone of synthesis (1000–220).
2. Zone of balance (220–20).
3. Zone of stable methane (20–0).
4. Oxidation zone (over daylight surface).
For every zone the description and explanations are given.
Data for 171 gas, gas-condensate and oil and gas-condensate fields of the DnieperDonets Depression were worked out. Calculation of balanced depths of formation was
carried out for 118 fields.
We have compiled maps-diagrams of depth fields for the Dnieper-Donets Depression
using two methods of interpolation: triangulation with further linear interpolation and polynomial interpolation.
The method of polynomial regression has allowed us to show an even increase in the
value of balanced depth in the north-western direction from 80 to 150 km, that is to say,
gradual dipping of the zone of balance.
Using the method of triangulation, it was possible to depict local complications of the
position and configuration of the zone of balance. Some of complications have concentric
closed contours; moreover such circular forms may be both “negative” and “positive”.
We have constructed the graph of the distribution of formation depths for fields of the
Dnieper-Donets Depression which has two marked maxima: for depth close to 115 and
140 km, and one slightly marked: for depths between 170–180 km.